VIRTUAL REALITY HYPNOSIS PADA TATALAKSANA PASIEN LANJUT USIA DENGAN ORAL FRAILTY: LAPORAN KASUS - Bakti, Fitrah Utari; Zakiawati, Dewi; Shafuria, Amira; Yubiliana, Gilang; Nur’aeny, Nanan (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2023)
Introduction: Oral frailty is a geriatric syndrome characterised by a decline in oral function associated with a decline in cognitive and physical function. Virtual reality hypnosis (VRH) is a current method that combines the benefits of virtual reality (VR) technology and hypnosis. Aim: This case report aims to describe the role of VRH in the management of elderly patients with oral frailty. Case and Management: A 65-year-old male patient came to the Oral Medicine Department with a chief complaint of dry mouth for the past three months. The patient often felt stressed because of his health problems. Intraoral examination showed frothy saliva, white plaque on the buccal and lateral mucosa of the tongue, missing teeth, and poor oral hygiene. Some additional examinations performed included the Indonesian Version of Summated Xerostomia Inventory (SXI-ID), Clinical Oral Dryness Score (CODS), sialometry, Depression Anxiety Stress Scale (DASS-21), and D-E-N-T-A-L oral frailty questionnaire. The test results showed that the patient had oral frailty. Case Management: Pharmacological therapy consisted of chlorine dioxide mouthwash, sucralfate syrup, and probiotic caplets. Non-pharmacological therapy consisted of instructions to maintain good oral hygiene, adopt a healthy lifestyle, and VRH. The relaxing effect of VRH was evidenced by the recording of increased alpha waves on quantitative electroencephalography (qEEG) during the procedure, and the results of SXI-ID, CODS, and DASS-21 at the last visit were normal. Oral frailty resolved after two weeks of treatment. The patient was also referred for oral care from the Departments of Periodontia, Prosthodontia, and Oral Surgery. Conclusion: VRH has an important role especially in the management of stress-induced xerostomia and pain in elderly patients with oral frailty.